Des Néerlandaises engagées dans le terrorisme transnational des années 1970 - Seran De Leede (Cahiers d’histoire)
Women are often underrepresented in the literature on political violent groups. This paper contributes to the literature on women in political by analyzing the biographies of four women who were involved in the Dutch radical Left-Wing group De Rode Jeugd. It identifies driving factors of their radicalization, their roles in the group, their stance towards the use of violence, their disengagement and their post-revolutionary life.